Modeling of Moisture Adsorption Isotherm of Selected Commercial flours of Bangladesh (The Agriculturists, 2018)
The moisture adsorption behavior is a fundamental knowledge in the processing and storage of food materials. In this paper, the experimental adsorption behavior of wheat, rice and corn flours were compared with five widely recommended adsorption models (BET, GAB, Oswin, Smith and Halsey) in the literature. From the sorption data, monolayer moisture content of wheat, rice and corn flours were estimated as per BET and GAB models. For all flours, GAB model gave higher monolayer moisture content compare to the BET model. Linear regression analysis was done to determine the model constants where all models were compared using regression coefficient and standard error of the estimate. It was observed that there is no single model that could describe accurately the sorption isotherm over the whole range of water activity (aw) and for all types of flours. BET model was found as the best model for the prediction of equilibrium moisture content (EMC) of the most stable region (i.e. EMC corresponding to aw range below 0.52) but it was not suitable at aw above 0.52. The GAB model was found to be the most suitable to predict the EMC for wide range of water activity (0.11 to 0.93).The Agriculturists 2018; 16(2) 35-42